(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The term Mobile Ad hoc Network refers to a network in which the nodes are mobile andengage in multi-hop communication with one another (MANET). With the use of MANETs, issues like dataloss and network congestion can be avoided in a number of different contexts. A major problem withmobile ad hoc networks is the poor quality of service they provide. The mobile ad hoc network is a selfconfiguringsystem in which mobile nodes can freely enter and exit the network. The main problem thatneeds to be fixed is routing, which is highly unstable due to the dynamic nature of the network. There arethree main types of routing protocols reactive, proactive, and hybrid. The AODV routing protocol is usedto set up a safe and efficient route from the source to the destination. Network link failure degrades theefficiency of the routing protocol. With the help of this study, we are able to modify the AODV protocoland significantly lessen the likelihood of a network link failing. The suggested method efficientlyrecovers the path between the source and the destination and keeps network quality constant. Thesuggested method is developed, and current algorithms are compared against it on a set of metrics..